Breastfeeding, Attachment, dan Attention Deficit Hyperactivity Disorder (ADHD) pada Perkembangan Anak - Ahmad Sudi Pratikno; Sumantri Sumantri (Auladuna : Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2022)
ABSTRACT (ENGLISH) Breastfeeding, attachment, and attention deficit hyperactivity disorder are three things that very related in child development. Breastfeeding is an activity to children starting from the age of 0-2 years, while breastfeeding that is really done completely and uninterruptedly, it will create attachment between the biological mother and her biological child. This is even until the child grows up. The impact that occurs if breastfeeding and attachment is not optimal or even does not appear, there will be a pattern of ADHD behavior, namely ADHD behavior pattern that is over activity, subsequently the child cannot be quiet. ABSTRAK (INDONESIA) Breastfeeding, attachment, dan attention deficit hyperactivity disorder adalah tiga hal yang sangat berkaitan dalam perkembangan seorang anak. Breastfeeding adalah kegiatan menyusui pada anak yang dimulai dari usia 0-2 tahun, sedangkan breastfeeding yang benar-benar dilakukan secara utuh dan tanpa terputus, maka akan menciptakan attachment (kemelekatan) antara sang ibu kandung kepada anak kandugnya. Hal ini bahkan sampai anak beranjak dewasa. Dampak yang terjadi jika breastfeeding dan attachment ini tidak maksimal atau bahkan tidak muncul, maka akan timbul pola perilaku ADHD, yakni pola perilaku anak yang aktif namun overdosis, sehingga anak tersebut tidak bisa diam.